Results of tectonic epikeratoplasty in the management of corneal perforations - Machowicz-Matejko, Eulalia; Rakowska, Ewa; Zagórski, Zbigniew (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To present therapeutic application of tectonic epikeratoplasty as biological patch in severe ocular surface disorders. Material and methods: Full thickness corneo-scleral transplants, 14 mm in diameter were used in 67 operations of 41 patients with corneal perforation or descemetocele. (14 women and 27 men), in the period 1998-2008. The mean age of patients was 55.2 ± 17.7 years (range 15-82). The transplants were sutured over the limbus or the scleral rim and was implanted under the conjunctiva after 360° peritomy. Donor tissue unsuitable for penetrating keratoplasty because of poor endothelium or corneal scarring, was obtained from Lublin Eye Bank. Results: We observed closing of the perforation in all cases. Healing of the ulceration with scar formation and new vessels ingrowth was noted. In some eyes repeated epikeratoplasties were performed. Conclusions: Tectonic epikeratoplasty is a safe and simple method of treatment of corneal perforations. It provides a biological patch stimulating the healing of corneal defects. It gives time for systemic treatment before further ocular surface reconstructive procedures can be performed.